Neonatal Bartter syndrome: A case report from Northern India - Singh, Astitva; Sharma, Nishant; Agarwal, Prachi; Anand, Bolledu Swaroop; Shukla, Akshay (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Bartter Syndrome is a rare genetic disorder affecting the renal tubular system causing a decreased absorption of sodium and chloride in the thick ascending limb of the Henle loop. Most children present in infancy with complaints of polyuria, polydipsia, vomiting, constipation and failure to thrive while older children present with recurrent episodes of dehydration, muscle weakness and cramps. The present study aimed to demonstrate a case of Bartter syndrome presenting as acute gastroenteritis.